Outcomes with allogeneic hematopoietic stem cell transplantation in TP53-mutated acute myeloid leukemia: a systematic review and meta-analysis. Issue 14 (6th December 2022) - Shahzad, Moazzam; Tariq, Ezza; Chaudhary, Sibgha Gull; Anwar, Iqra; Iqbal, Qamar; Fatima, Huda; Abdelhakim, Haitham; Ahmed, Nausheen; Balusu, Ramesh; Hematti, Peiman; Singh, Anurag K.; McGuirk, Joseph P.; et al.
Abstract: We conducted a systematic review and meta-analysis to evaluate outcomes after allogeneic hematopoietic stem cell transplantation (HSCT) in TP53-mutated acute myeloid leukemia (AML). We performed a literature search on PubMed, Embase, Cochrane Library, and ClinicalTrials.gov. After screening 592 manuscripts, eight studies were included. Data were extracted following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. Pooled analysis was done using the meta-package by Schwarzer et al. Proportions with 95% confidence intervals (CIs) were computed. We analyzed 297 patients. The median follow-up was 45 (0.9–407.3) months. The pooled 2-year overall survival was 29.7% (95% CI 0.17–0.43, n  = 82/248). The pooled relapse rate was 61.4% (95% CI 0.41–0.79, n  = 139/247) at a median follow-up time of 2 (0.26–3) years. Three-year progression-free survival and non-relapse mortality were reported by one study as 7.5% and 32.5%, respectively. Outcomes of HSCT for TP53-mutated AML are poor; however, HSCT confers a survival advantage as compared to non-transplant palliative therapies.